Turismo e políticas públicas na Amazônia brasileira - Maria Goretti da Costa Tavares (Confins)
Taking into account the implementation of specific tourism policies, from the 1970s onwards, the federal government carried out a series of measures aimed at expanding activity in the Amazon, among them, specifically, were the development plans of the region, or PDAS (the tourism plans of Amazonia I and II). In these plans, the spatial strategies were outlined in a very broad way, and above all the conception of development to which the Amazon region was subordinated. In this perspective, this article discusses the public tourism policies implemented for the region from the 1970s on, taking as an example the State of Pará. Finally debating the limits and possibility of tourist practices in the region.